Urban Acupuncture in Large Cities: Filtering Framework to Select Sensitive Urban Spots in Riyadh for Effective Urban Renewal - Nassar, Usama Abd Elhameed (Alanya Üniversitesi, 2021)
New revitalization and regeneration strategies are currently taking place as a scheme for reassessing urban spaces. This paper, as a result, navigates the theory of Urban Acupuncture (UA) as a quick and effective tool that can be adopted in large cities. Using Riyadh city as a case study, it discusses how this tool can be used to achieve maximum results with minimal effort in the most critical places. Riyadh city is the capital of Saudi Arabia and is considered one of the fastest-growing metropolitan cities in the Arab world. Through time, it has transformed into a city with leftover open spaces and an ever-increasing population. The study commences by exploring the term UA and its principles and similarly presents some of its successful international examples. It thereafter delves into the past and current situation in the city to show some of the challenges it faces. The study aims to develop a filtering framework for selecting a suitable sensitive spot that can be used to apply the concept of UA. A conclusion is made that as a small-scale space approach and a progressive concentrated urban renewal strategy.